Case Study On Law Enforcement Against Sexual Violence in Educational Environments - Nur Rois; Lena Claudia Angwarmasse; Folman P Ambarita (Journal of Strafvordering Indonesian, 2025)
Sexual violence in higher education is a critical legal and social issue requiring interdisciplinary responses. This study examines law enforcement against sexual violence in Indonesian universities through case studies of Universitas Gadjah Mada (UGM) and Universitas Mataram (UNRAM) using a mixed legal–sociological approach. Data were collected through document analysis, policy review, and academic literature synthesis. Findings reveal that although Law No. 12/2022 on Sexual Violence and Ministerial Regulation No. 30/2021 provide a progressive legal framework, implementation remains constrained by institutional hierarchy, cultural resistance, insufficient trauma-informed capacity, and limited coordination with law enforcement. Both cases demonstrate gaps between legal norms and university practices, particularly regarding victim protection, confidentiality, and administrative response. Strengthening campus task forces, establishing secure reporting mechanisms, ensuring structured collaboration with law enforcement, and mainstreaming gender-awareness education are crucial for creating safe academic environments and achieving substantive justice for victims.